Intensity of the immunity against measles in employees of the maternity unit in Moscow - M. P. Kostinov; P. I. Zhuravlev; D. V. Pakhomov; A. D. Shmit’ko; V. B. Polishchuk; N. N. Filatov; L. S. Gladkova; A. A. Ryzhov (Вопросы вирусологии, 2020)
Introduction. Measles remains an urgent problem in Russian healthcare. Despite the ongoing vaccination, there is an increase in the incidence of measles. Prevention of measles is particularly important in high-risk groups, as well as among healthcare professionals to prevent hospital-acquired outbreaks of infection. The duration of post-vaccination immunity during the elimination of measles has not been sufficiently studied, so often people who  have had measles in childhood or have 1–2 vaccinations against the disease lose their protective antibodies with age in the absence of natural boosterization.